Validação do modelo R.Sun para a estimativa da irradiação solar na bacia hidrográfica do Rio Negro - (:unkn) unknown (Universidade Federal do Pampa, 2016)
O objetivo do presente estudo é realizar a validação do modelo r.sun que realiza simulações de insolação e radiação global na plataforma GRASS GIS para estimar o potencial solar na bacia hidrográfica do Rio Negro, Rio Grande do Sul. As simulações de radiação global diária foram realizadas para dezesseis dias, extraídos ao longo de um período de um ano. Para a validação do modelo comparou-se os valores de radiação global diária simulados com os valores registrados na estação meteorológica automática Bagé-A827 do INMET. Como resultado do desenvolvimento da pesquisa, foram gerados os mapas de elevação, de declividade, de aspecto, de distribuição espacial da radiação global diária e de distribuição espacial da insolação diária, para a área de abrangência da bacia hidrográfica. O valor máximo de irradiação global diária encontrado foi de 9500,00 Wh/m² no solstício de verão, enquanto o valor mínimo foi de 3246,00 Wh/m², no solstício de inverno. A insolação diária apresentou valores mínimos de 9,32 h no inverno e valores máximos de 13,66 h no verão.

The objective of the present study is to estimate the photovoltaic potential in the Rio Negro basin, Rio Grande do Sul, from computational models and geoprocessing techniques. For this, the R.SUN model was used, which performs simulations of solar radiation and global radiation on the GRASS GIS platform. The simulations of daily global radiation and insolation had been performed for sixteen days over a period of one year. The simulated daily global radiation values were compared with the values recorded in the INMET Bagé-A827 automatic climatological station. As a result of the research development, maps of elevation, slope, aspect, spatial distribution of daily global radiation and spatial distribution of daily sunshine were generated for the area covered by the river basin. The maximum value of daily global radiation found was 9500,00Wh / m² in the summer solstice, while the minimum value was 3246,00Wh / m², in the winter solstice. The daily insolation presented minimum values of 9.32h in the winter and maximum values of 13.66h in the summer. The values for the simulated daily global radiation were, in general, higher than the values recorded by the INMET climatological station during the study period. Keywords
Keywords: Radiação solar; Grass gis; R.sun; Solar radiation; Simulation; R.sun